2021
DOI: 10.1038/s41541-021-00409-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of glycan chain length and linkage type on the immunogenicity of glycoconjugate vaccines

Abstract: The development and use of antibacterial glycoconjugate vaccines have significantly reduced the occurrence of potentially fatal childhood and adult diseases such as bacteremia, bacterial meningitis, and pneumonia. In these vaccines, the covalent linkage of bacterial glycans to carrier proteins augments the immunogenicity of saccharide antigens by triggering T cell-dependent B cell responses, leading to high-affinity antibodies and durable protection. Licensed glycoconjugate vaccines either contain long-chain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…Although NPs have been demonstrated to inhibit the activation of several inflammatory signaling pathways, no direct evidence of SCFAs produced by NPs fermentation with inflammatory responses or expression of peroxisome proliferator-activated receptor has been presented. In addition, glycan chain length and linkage type have been found to influence the immunogenicity and efficacy of glycoconjugate vaccines [130]; however, their structure-activity relationship in terms of IBD remains poorly understood. Furthermore, the bioavailability of NPs should be investigated to better understand their utilization in human body.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Although NPs have been demonstrated to inhibit the activation of several inflammatory signaling pathways, no direct evidence of SCFAs produced by NPs fermentation with inflammatory responses or expression of peroxisome proliferator-activated receptor has been presented. In addition, glycan chain length and linkage type have been found to influence the immunogenicity and efficacy of glycoconjugate vaccines [130]; however, their structure-activity relationship in terms of IBD remains poorly understood. Furthermore, the bioavailability of NPs should be investigated to better understand their utilization in human body.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The coupling of specific capsular polysaccharides to an immunogenic carrier protein provides induction of both B‐cell and T‐cell immunity leading to an improved long‐term immune response 2 . Anish et al 3 reported that long‐chain polysaccharides that are cross‐linked to the carrier protein medium‐length polysaccharides in an end‐linked configuration typically provide the highest immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…and culture conditions (pH, temperature, oxygen tension, etc.) [ 56 ] in order to consider that all fermentation performances were maintained under the k L a criterion scale-up process. The results in Table 3 showed that the PRP obtained presents an average MW about 347.2 kDa, while the MW of native PRP reported in a previous study was found between 450 and 600 kDa [ 55 ].…”
Section: Discussionmentioning
confidence: 99%